Skin boosters: Definitions and varied classifications - Yi, Kyu‐Ho; Winayanuwattikun, Waranaree; Kim, Sung‐Yeon; Wan, Jovian; Vachatimanont, Vanravi; Putri, Ardhiah Iswanda; Hidajat, Inneke Jane; Yogya, Yuri; Pamela, Ruri (Skin research and technology, 2024)
Background The concept of “skin boosters” has evolved, marking a shift from traditional uses of hyaluronic acid (HA) fillers primarily for augmenting skin volume to a more diverse application aimed at improving dermal conditions. Restylane Vital and other HA fillers have been repurposed to combat skin aging and wrinkles by delivering HA directly to the dermis. Objectives This review aims to define the term “skin booster” and to discuss the various components that constitute skin boosters. It seeks to provide a comprehensive overview of the different ingredients used in skin boosters, their roles, and their impact on enhancing dermal conditions. Methods A comprehensive review was conducted, focusing on representative skin booster ingredients. The approach involved analyzing the different elements used in skin boosters and their specific roles in enhancing dermal improvement. Results The findings indicate that skin boosters, encompassing a range of ingredients, are effective in improving the condition of the skin's dermis. The review identifies key ingredients in skin boosters and their specific benefits, including hydration, elasticity improvement, and wrinkle reduction. Conclusions Skin boosters represent a significant development in dermatological treatments, offering diverse benefits beyond traditional HA fillers. This review provides valuable insights into the constituents of skin boosters and their effectiveness, aiding readers in making informed decisions about these treatments. The potential of skin boosters in dermatological practice is considerable, warranting further research and application.